Sociální a ekonomické změny v životě bulharských "občanů cikánského původu" (1944 - 1989) - Stojanova, Plamena (Romano džaniben, 2016)
The article discusses the changes in the lives of the Romani population during the period 1944–1989. Education, work (employment) of Roms and housing issues concerning them are thoroughly construed in terms of state policies aiming at changes in their lives. The results and consequences of the policies implemented during the 45 years are critically assessed and analysed. The article is based mostly on archival documents.